Clinical outcome after mechanical thrombectomy in non-elderly patients with acute ischemic stroke in the anterior circulation: primary admission versus patients referred from remote hospitals - Pfaff, Johannes; Pham, Mirko; Herweh, Christian; Wolf, Marcel; Ringleb, Peter A.; Schönenberger, Silvia; Bendszus, Martin; Möhlenbruch, Markus Alfred (Clinical neuroradiology, 2017)
Background and PurposeStroke networks have been installed to increase access to advanced stroke specific treatments like mechanical thrombectomy (MT). This concept often requires patients to be transferred to a comprehensive stroke center (CSC) offering MT. Do patient referral, transportation, and logistic effort translate into clinical outcomes comparable to patients admitted primarily to the CSC?Material and MethodsWe categorized 112 patients with acute ischemic stroke in the anterior circulation, who received MT at our institution, into primary admissions (A) and referrals from either local (B) or regional (C) hospitals, assessed the clinical outcome, and tested the impact of distance and delay of transportation from the referring remote hospital.ResultsThe median time from symptom onset to initial CT was similar in all groups (p = 0,939). Patients who were transferred to the CSC had significantly increasing median time between initial CT and MT (in minutes (interquartile range [IQR]); A: 83 [68-120]; B: 174 [159-208]; C: 220 [181-235]; p < 0.001) and median time between onset to MT (in minutes [IQR]; A: 178 [150-210]; B: 274 [238-349]; C: 293 [256-329]; p < 0.001).After 90 days of MT there was no significant difference in clinical outcome (modified Rankin Scale ≤ 2) between primary admitted and referred patients (p = 0.502).ConclusionClinical outcome in patients who received MT after transfer from either local or regional remote hospitals was not significantly worse than in patients primarily admitted to the CSC. In the event of an acute ischemic stroke patients living in urban or rural areas should, despite a possible delay, have access to MT.